2021
DOI: 10.3390/jcm10020225
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Vessel Wall Magnetic Resonance Imaging of Small Unruptured Intracranial Aneurysms

Abstract: Background: We decided to investigate whether aneurysm wall enhancement (AWE) on high-resolution vessel wall magnetic resonance imaging (HR VW-MRI) coexists with the conventional risk factors for aneurysm rupture. Methods: We performed HR VW-MRI in 46 patients with 64 unruptured small intracranial aneurysms. Patient demographics and clinical characteristics were recorded. The PHASES score was calculated for each aneurysm. Results: Of the 64 aneurysms, 15 (23.4%) showed wall enhancement on post-contrast HR VW-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 41 publications
3
18
0
1
Order By: Relevance
“…It is also presumed to be an imaging marker of aneurysm instability, indicating lesions with higher risk of rupture [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. This hypothesis is consistent with the results of our previous study, in which we have shown a statistically significant association between AWE and conventional risk factors for aneurysm rupture [27]. Similar to our previous study, most of Tomography 2022, 8 304 the published literature on the use of HR-VW MRI in patients with intracranial aneurysms focuses on unruptured intracranial aneurysms (UIA) and determining whether AWE is an imaging marker of aneurysm instability.…”
Section: Introductionsupporting
confidence: 91%
“…It is also presumed to be an imaging marker of aneurysm instability, indicating lesions with higher risk of rupture [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. This hypothesis is consistent with the results of our previous study, in which we have shown a statistically significant association between AWE and conventional risk factors for aneurysm rupture [27]. Similar to our previous study, most of Tomography 2022, 8 304 the published literature on the use of HR-VW MRI in patients with intracranial aneurysms focuses on unruptured intracranial aneurysms (UIA) and determining whether AWE is an imaging marker of aneurysm instability.…”
Section: Introductionsupporting
confidence: 91%
“…The ISUIA study showed that the risk of rupture in UIAs smaller than 7 mm was low, and the role of HR-VWI in evaluating aneurysms smaller than 7 mm remained unclear. In our study, 25.3% (21/83) aneurysms showed wall enhancement, and 9.6% (8/83) showed CAWE, which was similar to previous studies investigating small UIAs (Zhu et al, 2018;Zwarzany et al, 2021). Zhu et al (2018) found that AWE was an independent predictor of ruptured aneurysms, and CAWE was significantly associated with ruptured aneurysms instead of AWE in aneurysms smaller than 7 mm.…”
Section: Discussionsupporting
confidence: 90%
“…VW-MRI may depict these processes and aneurysm wall enhancement (AWE) extent has been associated with the degree of histological inflammatory markers, as well as atherosclerosis, neovascularization, and macrophage infiltration [ 8 , 99 , 100 ].…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…VW-MRI has demonstrated its utility in a wide range of clinical situations, including differential diagnosis of intracranial vasculopathies, identification and evaluation of intracranial atherosclerotic disease and also risk stratification in patients with intracranial aneurysms [ 7 , 8 ]. When applied to patients with cryptogenic stroke, it allows for the definition of the stroke etiology in a significant percentage of them, often revealing findings compatible with vasculitis or complicated atherosclerotic disease [ 9 ].…”
Section: Introductionmentioning
confidence: 99%